Experimental Study: The Effect of Problem-Based Learning on Students' Chemistry Learning Outcomes in Thermochemistry Concepts - Sony Hidayat; Olaitan Abiodun Josiah (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to determine the effect of the Problem-Based Learning model on students’ chemistry learning outcomes, specifically on thermochemistry concepts, by comparing the performance of students taught using problem-based learning and those taught using conventional learning methods. Methodology: This study used a quasi-experimental method with a nonequivalent control group design. The sample was selected using purposive sampling. Data were collected using multiple-choice test instruments. Data analysis techniques included Liliefors normality test, Fisher homogeneity test, and t-test at a significance level of 0.05. Main Findings: The results showed that there was a significant difference in learning outcomes between students taught using the Problem-Based Learning model and those taught using conventional methods. Students in the experimental group demonstrated higher achievement in thermochemistry concepts compared to the control group after the learning process. Novelty/Originality of this study: This study provides new insights by applying an experimental design to specifically examine the effect of Problem-Based Learning on thermochemistry learning outcomes. It integrates contextual problem-solving with conceptual understanding, offering a more meaningful learning approach and contributing to the development of innovative chemistry teaching strategies.